2013
DOI: 10.1155/2013/460651
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of GMAW Process Parameters Using Particle Swarm Optimization

Abstract: To improve the corrosion-resistant properties of carbon steel cladding process is usually used. It is a process of depositing a thick layer of corrosion resistant material-over carbon steel plate. Most of the engineering applications require high strength and corrosion resistant materials for long-term reliability and performance. By cladding, these properties can be achieved with minimum cost. The main problem faced in cladding is the selection of optimum combinations of process parameters for achieving qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…for obtaining minimum dilution and optimal bead geometry using particle swarm mization [28] and ANN integrated with genetic algorithm [29].…”
Section: Plan Of Investigationmentioning
confidence: 99%
See 1 more Smart Citation
“…for obtaining minimum dilution and optimal bead geometry using particle swarm mization [28] and ANN integrated with genetic algorithm [29].…”
Section: Plan Of Investigationmentioning
confidence: 99%
“…They developed an optimization model and a prediction model for characteristics such as bead geometry and Dilution percentage. The research proposed optimal input param-eters for obtaining minimum dilution and optimal bead geometry using particle swarm optimization [28] and ANN integrated with genetic algorithm [29].…”
Section: Introductionmentioning
confidence: 99%
“…Yadav et al [15] made parametric optimization tensile strength in GMAW by performing Taguchi method. Sreeraj et al [16] made an optimization study for gas metal arc welding parameters using central composite rotatable design and particle swarm method. Shao et al [17] developed a mathematical model using design of experiments and polynomial regression method for modeling and optimization of gas metal arc welding method.…”
Section: Introductionmentioning
confidence: 99%
“…Patel and Chaudhary (2013) used the Design of Experiment method and grey relational analysis for optimizing the MIG and TIG welding parameters, they also used ANOVA for calculating quality characteristics. Sreeraj et al (2013) presented an experimental study to optimize various input process parameters to found the optimum dilution in stainless steel cladding of low-carbon steel plates which was welded by arc welding. Experiments were performed based on central composite rotatable design with full replication technique and using the multiple regression method with PSO technique to optimize the parameters to get minimal dilution.…”
Section: Introductionmentioning
confidence: 99%